Energy-Dense Formulae May Slow Gastric Emptying in the Critically Ill. (September 2016) - Kar, Palash; Plummer, Mark P.; Chapman, Marianne J.; Cousins, Caroline E.; Lange, Kylie; Horowitz, Michael; Jones, Karen L.; Deane, Adam M.
Background: Enteral feed intolerance occurs frequently in critically ill patients and can be associated with adverse outcomes. "Energy-dense formulae" (ie, >1 kcal/mL) are often prescribed to critically ill patients to reduce administered volume and are presumed to maintain or increase calorie delivery. The aim of this study was to compare gastric emptying of standard and energy-dense formulae in critically ill patients. Methods : In a retrospective comparison of 2 studies, data were analyzed from 2 groups of patients that received a radiolabeled 100-mL "meal" containing either standard calories (1 kcal/mL) or concentrated calories (energy-dense formulae; 2 kcal/mL). Gastric emptying was measured using a scintigraphic technique. Radioisotope data were collected for 4 hours and gastric emptying quantified. Data are presented as mean ± SE or median [interquartile range] as appropriate. Results : Forty patients were studied (n = 18, energy-dense formulae; n = 22, standard). Groups were well matched in terms of demographics. However, patients in the energy-dense formula group were studied earlier in their intensive care unit admission ( P = .02) and had a greater proportion requiring inotropes ( P = .002). A similar amount of calories emptied out of the stomach per unit time ( P = .57), but in patients receiving energy-dense formulae, a greater volume of meal was retained in the stomach ( P = .045), consistent with slower gastric emptying. Conclusions : In critically ill patients, the administration of the same volume of a concentrated enteral nutrition formula may not result in the delivery of more calories to the small intestine over time because gastric emptying is slowed.